Blood glucose control in diabetes patients seen in primary health care centers Controle glicêmico em pacientes diabéticos atendidos em centros de atenção primária à saúde - Maria Cecília F Assunção; Iná S Santos; Neiva C J Valle (Universidade de São Paulo, 2005)
OBJECTIVE: To identify factors associated to poor glycemic control among diabetic patients seen at primary health care centers. METHODS: A cross-sectional study was carried out in a sample of 372 diabetic patients attending 32 primary health care centers in southern Brazil. Data on three hierarchical levels of health unit infrastructure, medical care and patient characteristics were collected. RESULTS: The frequency of poor glycemic control was 50.5%. Multivariate analysis (multilevel method) showed that patients with body mass indexes below 27 kg/m², patients on oral hypoglycemic agents or insulin, and patients diagnosed as diabetic over five years prior to the interview were more likely to present poor glycemic control when compared to their counterparts. CONCLUSIONS: Given the hierarchical data structuring, all associations found suggest that factors associated to hyperglycemia are related to patient-level characteristics. OBJETIVO: Identificar fatores associados à falta de controle glicêmico em pacientes diabéticos atendidos em centros de atenção primária à saúde. MÉTODOS: Estudo transversal em amostra de 372 pacientes diabéticos atendidos nos 32 centros de atenção primária de uma cidade do sul do Brasil. Foram coletados dados ordenados em três níveis hierárquicos: estrutura das unidades de saúde, características do processo do cuidado médico e pacientes diabéticos. RESULTADOS: A freqüência de falta de controle glicêmico foi de 50,5%. A análise multivariada (método multinível) mostrou que pacientes com Índice de Massa Corporal abaixo de 27 kg/m², em tratamento medicamentoso e com mais de cinco anos de diagnóstico de diabetes, tiveram maior probabilidade de apresentar hiperglicemia quando comparados a seus pares. CONCLUSÕES: Considerando a estrutura hierárquica dos dados, todas as associações encontradas sugerem que os fatores associados à hiperglicemia são relacionados a características dos pacientes.